ChemInform Abstract: Diethylene Glycol Serving as Ethyne Equivalent: A Sustainable Approach Toward 2, 3‐Disubstituted Furan. Issue 50 (December 2015) - Yu, Jin‐Tao; Shi, Bo; Peng, Haibo; Sun, Song; Chu, Haoke; Jiang, Yan; Cheng, Jiang
Abstract: A copper‐catalyzed annulation of ethylene glycol with various 1, 3‐dicarbonyl compounds, including (hetero)arylacetoacetic esters, amides, ketones, and thioesters is elaborated which provides 2, 3‐disubstituted furans, mostly regioselectively, in moderate to high yields.